Assessment of Direct Payments in the Context of Information Flow and Farmers' Difficulties with Application - Czubak, Wawrzyniec (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2008)
After accession to EU direct payments have become the most important form of support for agricultural farms in Poland. The main aim of this article was to present an assessment of farmers’ difficulties in applying for direct payments. Access to information about payments was also examined. It was established that farmers had no problem getting the up-to-date information on direct payments, especially information on when and where to file their applications. However, part of beneficiaries had difficulties obtaining current information on how to fill out application forms. Farmers described the key elements of the required documentation as easy or very easy to prepare. The measurement of agricultural plots proved to be relatively the most difficult element. Generally, in the farmers’ opinion direct payments will not contribute greatly to an improvement in the condition of farms.
Keywords: direct payments; information; application form